The Effect of Sodium Channel Blocker, Mexiletine, on Body Weight in Type 2 Diabetes Patients with Visceral Obesity. (January 2019) - Ueno, Naohiko
Objective: Mexiletine is an anti-arrhythmic agent also used for the treatment of painful diabetic neuropathy. In this study, the effect of mexiletine on body weight was evaluated in type 2 diabetes patients with diabetic neuropathy exhibiting visceral obesity. Methods: Type 2 diabetes patients with neuropathy exhibiting visceral obesity (n = 21) treated by mexiletine (300 mg/day) and a control group of type 2 diabetes patients with the same condition who received vitamin B12 (n = 12) were retrospectively evaluated. Body weight, waist circumference, hemoglobin A1c (HbA1c), blood pressure, liver function, serum lipids, and serum uric acid were assessed before and 6 months after the treatment. Results: Mexiletine significantly decreased body weight and waist circumference. The changes in body weight and waist circumference in 6 months in the mexiletine group were greater than in the control group. In metabolic parameters, there were significant decreases in triglyceride (TG) and serum uric acid. There were positive relationships between the change in body weight and the changes in TG, uric acid, alanine aminotransferase (ALT), and HbA1c. Conclusions: Mexiletine may affect body weight regulation. It ameliorated the metabolic parameters possibly by decreasing visceral fat. Further study should be performed to clarify the mechanism of the effect.